2010
DOI: 10.1007/s13181-010-0074-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Predictors of Adverse Cardiovascular Events in Suspected Poisoning

Abstract: Poisoning is the second leading cause of injury-related fatality in the USA and the leading cause of cardiac arrest in victims under 40 years of age. The study objective was to define the electrocardiographic (ECG) predictors of adverse cardiovascular events (ACVE) complicating suspected acute poisoning (SAP). This was a case-control study in adults at three tertiary-care hospitals and one regional Poison Control Center. We compared 34 cases of SAP complicated by ACVE to 101 consecutive control patients with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 36 publications
5
29
0
Order By: Relevance
“…These findings are consistent with a prior study that demonstrated a strong association of ECG ischemia with adverse cardiovascular events in overdose patients [17]. In that prior study, components of the initial ECG were analyzed for the ability to predict cardiovascular events, and it was found that ECG evidence of ischemia was present in 40 % of patients who went on to have in-hospital cardiac arrest, versus 18 % of those who did not ( p < 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with a prior study that demonstrated a strong association of ECG ischemia with adverse cardiovascular events in overdose patients [17]. In that prior study, components of the initial ECG were analyzed for the ability to predict cardiovascular events, and it was found that ECG evidence of ischemia was present in 40 % of patients who went on to have in-hospital cardiac arrest, versus 18 % of those who did not ( p < 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…9 VF is probably the final common pathway of most sudden cardiac deaths, but rhythm disturbances may begin with monomorphic or polymorphic VT as well as torsade de pointes, 23 a form of polymorphic VT that is identified characteristically on the ECG. The dichotomization of QTc around 500 ms in this study, in lieu of the “QT nomogram,” 24 is justified by prior drug overdose data using this cutoff to predict ACVE, 8 as well as data from Chan and colleagues that demonstrated that the QT nomogram performed essentially the same as the 500 ms cutoff at predicting poisoning-related torsade de pointes (98.7% vs. 97.2% specificity, respectively). 24 This study demonstrates that VT/VF is much more common than torsade de pointes in this population, and that dysrhythmia occurrence may be predictable.…”
Section: Discussionmentioning
confidence: 94%
“…The final multivariable model was built around four separate conceptual clusters (defined a priori on the basis of clinical experience and prior data, 8 as demographic, clinical history, laboratory, and ECG variables) considered as separate groups to achieve a parsimonious and clinically meaningful model. Associations between clinical factors and the primary outcome were calculated first using univariate analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…QT prolongation is considered to be a reliable surrogate for the potentially fatal dysrhythmia known as torsades de pointes (TdP), because TdP is generally preceded by QT prolongation. Previously, QT prolongation has been identified as a strong predictor of adverse cardiovascular events in suspected poisoning from drug overdose (10). …”
Section: Introductionmentioning
confidence: 99%